Construction of Streptomyces coelicolor A3(2) mutants that exclusively produce NA4/NA6 intermediates of agarose metabolism through mutation induction - Jina Kim; Eun Joo Kim; Hye-Jeong Ko; Yeon-Hee Lee; Soon-Kwang Hong; Miyoung Shin; Je Hyeon Lee; Woori Kwak (Scientific Reports, 2023)
Abstract NA4/NA6, an intermediate degradation product of β-agarase, is a high value-added product with anticancer, anti-obesity, and anti-diabetic effects. Therefore, a method that enables the efficient production of NA4/NA6 would be useful from economic and medical perspectives. In this study, we aimed to generate a Streptomyces coelicolor A3(2) mutant M22-2C43 that produces NA4/NA6 as a final product; this method serves as a more efficient alternative to the enzymatic conversion of β-agarase for the generation of these products. The M22-2C43 strain was generated through two rounds of mutagenesis and screening for increased β-agarase activity and effective production of NA4/NA6. We assembled the complete genomes of two mutants, M22 and M22-2C43, which were identified following a two-round screening. Large and small genetic changes were found in these two mutants, including the loss of two plasmids present in wild-type S. coelicolor A3(2) and chromosome circularization of mutant M22-2C43. These findings suggest that mutant M22-2C43 can produce NA4/NA6 as a degradation product due to functional inactivation of the dagB gene through a point mutation (G474A), ultimately preventing further degradation of NA4/NA6 to NA2. To our knowledge, this is the first report of a microbial strain that can effectively produce NA4/NA6 as the main degradation product of β-agarase, opening the door for the use of this species for the large-scale production of this valuable product.